Make green growth a priority : issues and challenges in organising green sports tourism events / Lim Khong Chiu, Asmahany Ramely and Anisah Abdul Wafi - Lim, Khong Chiu; Ramely, Asmahany; Abdul Wafi, Anisah (Universiti Teknologi MARA, Perak, 2020)
Despite many sports tourism events have been organized globally yet the understanding about the event greening practices is reasonably low. Hence, the impact of the sports event towards the environment and the communities are exceptionally high. For the purpose of this paper, some academic and consultancy-based literature on management and organization of sports tourism events in relation to green growth were reviewed. This conceptual paper focuses on the conceptualization and implementation of green sports events which covers the theory and principles of green practices, strategies and implementation of green practices in the case of selected Olympic Games, issues and challenges, and the roles of stakeholders. In addition, the critical insight from the literature also provides some “green” suggestions to be considered by sports tourism event organisers.